2021
DOI: 10.3390/ma14154208
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of the Effect of Projectile Nose Shape on the Deformation and Energy Dissipation Mechanisms of the Ultra-High Molecular Weight Polyethylene (UHMWPE) Composite

Abstract: The effect of projectile nose shape on the ballistic performance of the ultra-high molecular weight polyethylene (UHMWPE) composite was studied through experiments and simulations. Eight projectiles such as conical, flat, hemispherical, and ogival nose projectiles were used in this study. The deformation process, failure mechanisms, and the specific energy absorption (SEA) ability were systematically investigated for analyzing the ballistic responses on the projectile and the UHMWPE composite. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Experimental results found that average energy absorption co-efficient increases with thickness. And shows different ballistic performance for different geometry of bullet [31].…”
Section: Problem Defining Criteria'smentioning
confidence: 98%
“…Experimental results found that average energy absorption co-efficient increases with thickness. And shows different ballistic performance for different geometry of bullet [31].…”
Section: Problem Defining Criteria'smentioning
confidence: 98%
“…It is a proper material for manufacturing various parts of machines, mechanisms and devices, shoulder and hip implants and for defective bone replacement along with polytetrafluoroethylene (PTFE) [1][2][3][4][5][6]. UHMWPE is highly resistant to impact, so it is also used for protection against penetration by metallic projectiles, especially when it is reinforced with various additives and inserts [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…These properties make UHMWPE the material of choice for a wide range of applications, such as chain guides, star wheels, truck beds, lead acid battery separators, as well as knee, shoulder and hip implants in modern medicine [ 2 , 3 ]. Owing to its high impact strength and toughness, UHMWPE is also used as armor protection [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%